Colorectal cancer and the blood loss paradox. Issue 5 (21st October 2021) - Almilaji, Orouba; Parry, Sally D; Docherty, Sharon; Snook, Jonathon
Abstract : Background: Faecal occult blood (FOB) positivity and iron deficiency anaemia (IDA) are common manifestations of colorectal cancer (CRC) and both potentially facilitate diagnosis at an earlier, more treatable stage. It has been assumed that both are the consequence of low-grade blood loss from the tumour bed. Method: A retrospective analysis of 1121 cases of CRC diagnosed at a single centre between 2010 and 2016, comparing cases presenting via FOB-based Bowel Cancer Screening Programme (BCSP) and IDA pathways for a series of variables including age, sex, tumour location and prevalence of anaemia. Results: The BCSP and IDA pathways each accounted for about 15% of the total case load. There were significant differences between the BCSP and IDA sub-groups in median age (68 vs 78 years: p<0.001), median haemoglobin (138 vs 89 g/L: p<0.001) and proportion of lesions in right colon (31.1% vs 82.5%: p<0.001). The major disparity in the prevalence of anaemia (overall 20.0% vs 98.2%: p<0.001) persisted when controlled for tumour location. Conclusion: Paradoxically, CRC screening through the detection of FOB positivity and IDA identifies distinctly different sub-populations of cases. The theoretical implication is that an additional mechanism may be required to explain the development of IDA in CRC. The practical implication is that detection of IDA may have a complementary role to the BCSP in population screening for CRC.